Understanding the packing in the 1 : 1 molecular complex 1, 3, 5-tricyanobenzene–hexamethylbenzene by probing lattice modes1. Issue 20 (28th May 2015) - Stride, John A.
<x xml:space="preserve">Abstract</x> Inelastic neutron scattering is used to directly probe the effect of intermolecular interactions in the text-book co-crystal hexamethylbenzene : tricyanobenzene.